PEMANFAATAN WEBDESIGN UNTUK PEMBUATAN SOSIAL MEDIA KOMUNITAS MOTORSTUDI KASUS FOKER CHAPTER PADANG - Sophan Sophian (ITP Press, 2017)
Federation Of Kawasaki Elite Rider one organization that is very known for its hospitality in a drive that is already a lot knowing that FOKER Chapter Padang one of the pioneers of the field organization of Motor which require to wear protective head in driving one of them give information about the surrounding activities. The registration process on Foker Chapter is far from optimal Pasture because the registration process is still manual, data storage is still shaped the archive so it takes a long time because they have to menyusunkembali data member based on the archives that have been kept. To resolve the problem, then the surveyors laid out the design of the Social Media websites based On FOKER CHAPTER Padang. The design of this website are a solution for Member registration process in order to be effective and efficient, archiving data members using computerized databases , so the data is more secure and avoid duplication of data and reporting process.